Biocompatible Material from Indonesian Natural Resource of Wild Silkmoth Cocoon - Nindhia, Tjokorda Gde Tirta; Knejzlík, Zdenek; Ruml, Tomáš; Surata, I Wayan; Nindhia, Tjokorda Sari (Advances in Tropical Biodiversity and Environmental Sciences; Vol 1 No 2 (2017): ATBESDO - 10.24843/ATBES.2017.v01.i02.p05, 2018)
Silk can be produced by spider or insect and have prospect as biomaterial for regenerative healing in medical treatment. Silk having physical and chemical properties that support biocompatibility in the living things..In this research, silk that was obtained from Indonesia natural resource of Attacus atlas silkmoth was explored and then will be  developed for biocompatible biomaterial. The treatment with NaOH was developed to separate the fiber from the cocoon. The obtained fiber is investigated its mechanical property by performing tensile test for single fiber. The biocompatibility testing was conducted with human cell (osteosarccoma) cultivation. The result identify that separation by using NaOH yield better better mechanical properties comparing konvenstional method with boiling in hot water. Biocompatibility testing indicate that the the fiber having good biocompatibility.